The European Union’s Approach to manage the crisis in the Sahel - Kebbabi, Saliha (Journal of Human Sciences, 2021)
The Sahel region in Africa has been exposed to several developments and security updates across different time periods, making it as a very important and complex space with a high acquired degree of security importance; because of various and overlapping reasons and elements that have made it a subject for eventual re-evaluation and possible rebuilding. However, it appears that the decision makers’ perceptions in Europe about threats coming from the south and the problems posed by the situation on the Sahel- region, push the European Union to reorder its security arrangements within its Neighboring borders. These are the arrangements that have resulted in a set of policies which has been known as the European Neighborhood Policy that aims to contain security threats, with a new map of security arrangements with different dimensions: economic, social, cultural and political.